Development of a home energy monitoring system using wireless communications - Lim, Tian Tian. (2012)
With the increasing concern over the rapidly depleting natural resources, there is a growing interest worldwide in sustainable energy technology. The ever-increasing energy cost made people realized the importance of energy conservation. However, it is insufficient to depend solely on the advancement to sustainable energy technology like solar and wind energy. Good energy usage habits have to be promoted and cultivated. Utilizing energy efficiently will allow savings to electrical bills and ultimately reduce the reliance on natural resources.